Eclosão de estágios dormentes de invertebrados aquáticos em áreas úmidas subtropicais e do semiárido brasileiro e suas implicações práticas na restauração ecológica - Vendramin, Daiane (Universidade do Vale do Rio dos Sinos, 2022)
Intermittent wetlands are among the most diverse and threatened environments in the world, being characterized by cycles of flooding and drought that directly influence the dynamics of their aquatic communities. Many wetland invertebrates adopt the production of dormant stages as strategy to resist the period of hydric stress. By performing the function of biotic reservoir, dormant stages contribute to the reestablishment of the community after flooding, and can be used in restoration initiatives over degraded wetlands. In this context, the main objective of this thesis was to assess the hatching dynamics adopted by dormant stages of aquatic invertebrates in subtropical and semiarid Brazilian wetlands, as well as to analyze the practical implications of using this community in wetland restoration efforts. In this sense, this work used the ex situ methodology of dry sediment hydration, with constant photoperiod, temperature and oxygenation. Also, sediment samples were collected in intermittent wetlands of the southern Brazilian Coastal Plain (12 study sites), in intermittent wetlands of the Brazilian tropical semiarid (six study sites), and in the floodplain wetlands of Rio dos Sinos (eight study sites). In the Coastal Plain, our results demonstrate that hatching dynamics of dormant stages are influenced by the sequential combination of hydration events. In the Brazilian semiarid, the short-term variation in hatchling community structure over a hydration period showed that the hatching dynamics of the invertebrate egg-bank is mostly composed by delayed-hatching strategies. Finally, an experimental study with the sediment of the Sinos River floodplain wetlands indicated the potential of transposing sediments with banks of invertebrate dormant stages to ecological restoration of mining-impacted wetlands. Our findings improve the knowledge about the hatching dynamics of aquatic invertebrates in subtropical and semiarid wetlands, contributing to restoration and conservation projects for Brazilian wetlands.
Keywords: Áreas úmidas intermitentes; Zooplâncton; Banco de estágios dormentes; Quebra de dormência; Restauração ecológica; Intermittent wetlands; Zooplankton; Egg banks; Dormancy breaking; Ecological restauration; ACCNPQ::Ciências Biológicas::Biologia Geral